Multiple Contracts: The Case of Periodic Balloon Payments – Constant Installments (London Journal of Research In Management & Business, 2025)
The practice of the game of chess leads to the development of skills related to memory, logic, concentration, rigor, strategy and the capacity for abstraction. In addition to the benefits observed on learning citizenship, by respecting the rules and others. Solving chess problems is an interesting variation for realizing intellectual development. The common way is to present problems on the chessboard or through diagrams. Here, we present a new method of solving chess problems based on a purely mathematical solution. Concretely, it is a question of solving a chess problem thanks to the solution of equations and the mathematical analysis. Thus with a basic knowledge of mathematics, generally of the secondary level, we can proceed to the resolution with a minimum of knowledge of chess, given that the resolution is done from the algebraic notation of the said problem. Here we advance definitions, properties and theorems.Also we present here an example of a chess problem solved by the method.
Keywords: Machine learning; Volatility; Pairs Trading; Clustering Algorithms; cryptocurrencies market; cointegration; algorithmic trading; trading strategies; market efficiency.